160k views
2 votes
From the previous step we have erx(6r2 + 3r − 3) = 0. Since erx is never 0, then we know 6r2 + 3r − 3 = 0. Solving the above equation gives the solutions to the quadratic equation.

2 Answers

4 votes

Answer:

r = - 1 or r = 1/2

Explanation:

From the quadratic equation;


6r^(2) + 3r - 3 = 0


6r^(2) + 6r - 3r - 3 = 0

(
6r^(2) + 6r) - (3r + 3) = 0

6r(r + 1) - 3 (r + 1) = 0

⇒ (r + 1) or (6r - 3) = 0

r + 1 = 0 or 6r - 3 = 0

r = - 1 or 6r = 3

r = - 1 or r = 1/2

Thus, the solutions to the equation are; r = - 1 or r = 1/2 since erx is never 0.

User Phedra
by
6.1k points
2 votes

Answer:

6r2+3r-3=0

two solutions are possible

r= -1

r=1/2

User Gammelgul
by
5.6k points